2016
DOI: 10.1002/joc.4742
|View full text |Cite
|
Sign up to set email alerts
|

Recent and future changes in the combination of annual temperature and precipitation throughout China

Abstract: Climate involves different combinations of temperature and precipitation, and each year's combination of factors can be assigned a climatic year type (CYT; e.g. Warm‐Humid). Describing the changes in the CYT provides more information than describing the temperature or precipitation data alone. In this study, we defined nine CYTs using the probability density function of annual temperature and precipitation. Recent and future spatiotemporal changes in CYT were analysed using 507‐station observational data and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 55 publications
6
26
0
Order By: Relevance
“…As produced by PRECIS, changes of the Tmean and Tmin during the 21st century would be in agreement with variability of the radiative forcing trajectories under RCP scenarios [34,35]. In comparison with the Tmean, the Tmin would warm up more obviously, which is consistent with previous findings [34,36]. Relative to observations, overestimation of the simulated …”
Section: Discussionsupporting
confidence: 89%
“…As produced by PRECIS, changes of the Tmean and Tmin during the 21st century would be in agreement with variability of the radiative forcing trajectories under RCP scenarios [34,35]. In comparison with the Tmean, the Tmin would warm up more obviously, which is consistent with previous findings [34,36]. Relative to observations, overestimation of the simulated …”
Section: Discussionsupporting
confidence: 89%
“…For consistency, the observations were also interpolated to the same grids (0.5° × 0.5°). The relative model error (RME * ) was defined for every model (Liu et al, ) by RME*=RMSERMSEfalse¯trueRMSE¯ where RMSE was the RMSEs of regional averaged T max , FHD, and FHW over NEC between each model and observation, trueRMSE¯ was the average value of RMSEs for the 22 GCMs. The negative RME * values indicated that the model performance was better than the majority (50%) of models and vice‐versa.…”
Section: Methodsmentioning
confidence: 99%
“…For consistency, the observations were also interpolated to the same grids (0.5 × 0.5 ). The relative model error (RME * ) was defined for every model (Liu et al, 2016) by…”
Section: Climate Change Scenariosmentioning
confidence: 99%
“…We compared the root‐mean‐square errors (RMSEs) of the regional averaged LSFD, FFFD, and LFFS over NEC, which were calculated by the observations and by the models, respectively. The relative model error ( RMSE *) (Liu et al , ) was defined for every model by RMSE*=RMSERMSEmeanRMSEmean …”
Section: Methodsmentioning
confidence: 99%
“…which were calculated by the observations and by the models, respectively. The relative model error (RMSE*) (Liu et al, 2017) was defined for every model by…”
Section: Evaluation Of the Performance Of Cmip5 Modelsmentioning
confidence: 99%